ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI ERA PANDEMI COVID-19 DITINJAU DARI TEORI KEMASLAHATAN - Swagumilang, Ken; Pudjihardjo, M (Islamic Economics and finance in Focus, 2023)
This study aims to Determine The Analysis Of Factors Influencing The Income Level Of Micro, Small And Medium Enterprises In The Covid-19 Pandemic Under The Perspective Of Kemashlahatan Theory: A case Study on UMKM Culinary at Kelurahan Landungsari, Kecamatan Dau, Malang. Using variables: Work time, Age, Capital dan Working experience and also study under perspective of kemashlahatan theory. This Study use 30 samples which include food and beverage enterprises. Data were collected by spreading questionnaires with purposive sampling methods. The results of this study indicate Work time variables have negative and significant effect, Age variables have negative and significant effect, meanwhile working experience dan capital have positive and significant effect